1999
DOI: 10.1063/1.123480
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of molecular organic semiconductor thin films under intense electrical excitation

Abstract: Articles you may be interested inAccumulation of electric-field-stabilized geminate polaron pairs in an organic semiconductor to attain high excitation density under low intensity pumping

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…Additional strong losses arise from quenching by the copious polarons, SEs, TEs, and the metal electrodes. [2][3][4][5][6] This presents a major obstacle in reaching the lasing threshold.…”
Section: Spectrally Narrowed Edge Emission From Organic Light-emittinmentioning
confidence: 99%
“…Additional strong losses arise from quenching by the copious polarons, SEs, TEs, and the metal electrodes. [2][3][4][5][6] This presents a major obstacle in reaching the lasing threshold.…”
Section: Spectrally Narrowed Edge Emission From Organic Light-emittinmentioning
confidence: 99%
“…Exciton-polaron annihilation is the most critical issue to overcome because all polarons have a broad absorption spectrum. [8][9][10][11] In our previous study, we demonstrated high current injection of over 1000 A cm À2 without device breakdown into OLEDs with an unusual device configuration of a small active area (200 Â 200 nm) on a high thermally conductive substrate by application of a short pulse voltage of less than 1 ls. 12,13 However, very serious efficiency roll-off was observed at such high current density.…”
mentioning
confidence: 99%
“…Within the OLED devices, however, inherent low carrier mobility of organics brings about the situation that the density of charge carriers ͑i.e., polarons͒ is much higher than that of emissive excitons, thereby causing a large absorption loss of stimulated emission by polarons. 7,8 Actually, in a thin film of tris-͑8-hydroxyquinoline͒ aluminum ͑Alq͒-doped with a DCM2 laser dye, which is a host-guest type of emitting layer enabling an efficient Förster energy transfer, it is shown that the optical gain of DCM2 cannot be obtained due to the absorption loss by large amounts of anionic Alq hosts. 7 The drastic raising of mobility enough to change such a situation could hardly be expected under the carrier-transport mechanism of organics described by hopping, so that the polaronabsorption problem is a serious obstacle to the realization of OLDs.…”
mentioning
confidence: 99%
“…7,8 Actually, in a thin film of tris-͑8-hydroxyquinoline͒ aluminum ͑Alq͒-doped with a DCM2 laser dye, which is a host-guest type of emitting layer enabling an efficient Förster energy transfer, it is shown that the optical gain of DCM2 cannot be obtained due to the absorption loss by large amounts of anionic Alq hosts. 7 The drastic raising of mobility enough to change such a situation could hardly be expected under the carrier-transport mechanism of organics described by hopping, so that the polaronabsorption problem is a serious obstacle to the realization of OLDs.One of the strategies for circumventing this problem is to design the device such that the gain spectrum of a laser dye has little overlap with the absorption spectra of charge carriers. 5 For this purpose, the use of the cascade Förster energy-transfer system that is formed by simultaneous doping of two or more guests into a host matrix 9 might be an effective way, since the gain wavelength can be widely changed by the combination of guests suitably matched in their absorption and emission spectra.…”
mentioning
confidence: 99%